Clostridioides difficile bile salt hydrolase activity has substrate specificity and affects biofilm formation - Andrea Martinez Aguirre; Adegoke Oyeleye Adegbite; Joseph A. Sorg (npj Biofilms and Microbiomes, 2022)
Abstract The Clostridioides difficile pathogen is responsible for nosocomial infections. Germination is an essential step for the establishment of C. difficile infection (CDI) because toxins that are secreted by vegetative cells are responsible for the symptoms of CDI. Germination can be stimulated by the combinatorial actions of certain amino acids and either conjugated or deconjugated cholic acid-derived bile salts. During synthesis in the liver, cholic acid- and chenodeoxycholic acid-class bile salts are conjugated with either taurine or glycine at the C24 carboxyl. During GI transit, these conjugated bile salts are deconjugated by microbes that express bile salt hydrolases (BSHs). Here, we surprisingly find that several C. difficile strains have BSH activity. We observed this activity in both C. difficile vegetative cells and in spores and that the observed BSH activity was specific to taurine-derived bile salts. Additionally, we find that this BSH activity can produce cholate for metabolic conversion to deoxycholate by C. scindens. The C. scindens-produced deoxycholate signals to C. difficile to initiate biofilm formation. Our results show that C. difficile BSH activity has the potential to influence the interactions between microbes, and this could extend to the GI setting.